KERJASAMA GURU BK DAN GURU MATA PELAJARAN/PRAKTIK MEMBANTU SISWA YANG MENGALAMI KESULITAN BELAJAR PADA MATA PELAJARAN PRODUKTIF AKUNTANSI - Ismawati, Ismawati; Alizamar, Alizamar; Nurfarhanah, Nurfarhanah (Konselor, 2013)
Productive Subject of Accounting is the main subject competency skills for students who continue their education at SMK Negeri 2 Padang majoring in Accounting. Difficulties of learning of students in productive subjects feared accounting students will increasingly have an impact on subsequent learning outcomes. Need the cooperation of BK teacher and subject teachers /practices to help students overcome these difficulties. In fact, help sought for students who have not yet obtained the results as expected. This study aimed to describe the cooperation that has been done by BK teacher and subject/practices teachers to help students who have difficulty learning in productive subjects in SMK Negeri 2 Padang.This research is a descriptive study with a qualitative approach. Subjects were a person who has as BK teachers and 3 subject/practices teacher given the task of fostering productive groups of subjects for class X Accounting Department of school year 2011-2012 in SMK Negeri 2 Padang. Researchers used data collection tool that statement list format (questionnaire), interview, tape recorders and digital cameras. The data were analyzed and elaborated qualitatively, questionnaire respondents through interviews and documentary study describe naratively. The findings of the study revealed that cooperation BK teachers and subject/practices teachers help sought for students who have difficulty learning in accounting subjects as a whole has been done, though not as expected.